Inclusão: análise das práticas pedagógicas do ciclo alfabetização do ensino fundamental de escolas municipais de Limeira-SP - Silva, Libia Sara Rocha Garcia da [UNESP] (2015)
The problem, this research focus, sum up in the following question: Do the pedagogical practices, performed in the literacy cycle of Elementary Education, meet the intellectually disabled students' learning needs in their process of school inclusion? According to the municipal schools teachers' reports, the index of failure in the learning among intellectually disabled students, included in the literacy cycle of Elementary Education is significant and worrisome. From the teachers' speaking, we sought to identify and analyze the pedagogical practices used by the teachers in the literacy cycle of Elementary Education with students in the process of inclusion and the contribution of such pedagogical practices to the learning process and school inclusion, which constitute the aims of this essay. For this purpose, we are going to observe what the most used criteria are to deal with the differences in class by teachers, considering the relation of these practices with the official prerequisites of the Inclusive Education. The research is performed in two stages. The first one consists of a bibliographical survey of theoretical framework and documents, among them the political pedagogical project and essays of several authors who argue about the matter of pedagogical practices, inclusion and literacy. The second one is composed of research reports done in regular municipal schools of Limeira/SP, by observing classrooms attended by intellectually disabled students and structured interviews with teachers of literacy cycle classrooms, being 11 participating teachers in 10 regular schools. The outcomes of this survey depict that the literacy, the included student's reading and writing learning, doesn't integrate the educator's work. This is evident in class due to the lack of teachers' commitment to the insertion of these activities, a point which gets worse faced with the possibility of these students, who took part in this research, ...